2021
DOI: 10.4143/crt.2021.031
|View full text |Cite
|
Sign up to set email alerts
|

Ferroportin and FBXL5 as Prognostic Markers in Advanced Stage Clear Cell Renal Cell Carcinoma

Abstract: PurposeAdvanced stage clear cell renal cell carcinoma (ccRCC) involves a poor prognosis. Several studies have reported that dysfunctions in iron metabolism‒related proteins may cause tumor progression and metastasis of this carcinoma. In this study, we investigated the impact of the expression of iron metabolism‒related proteins on patient prognoses in advanced stage ccRCCs. Materials and MethodsAll of 143 advanced stage ccRCC specimens were selected following validation with double blind reviews. Several clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…And FPN1 mRNA and protein expression are significantly downregulated, and patients with a low FPN1 expression have a poor prognosis in lung cancer and adrenocortical carcinoma (ACC) (178,183). Additionally, a similar effect was observed in multiple myeloma and ccRCC (43,184). Furthermore, STEAP3 is highly expressed in glioblastoma and is closely related to the decreased overall survival rate (39); however, a survival analysis showed that breast cancer patients with high levels of STEAP1, STEAP2, and STEAP4 had an overall good prognosis (185).…”
Section: Iron In Cancer Therapeutics Iron In Cancer Prognosismentioning
confidence: 93%
“…And FPN1 mRNA and protein expression are significantly downregulated, and patients with a low FPN1 expression have a poor prognosis in lung cancer and adrenocortical carcinoma (ACC) (178,183). Additionally, a similar effect was observed in multiple myeloma and ccRCC (43,184). Furthermore, STEAP3 is highly expressed in glioblastoma and is closely related to the decreased overall survival rate (39); however, a survival analysis showed that breast cancer patients with high levels of STEAP1, STEAP2, and STEAP4 had an overall good prognosis (185).…”
Section: Iron In Cancer Therapeutics Iron In Cancer Prognosismentioning
confidence: 93%
“…Previous studies using FBXL5 knockout mice revealed iron accumulation in the liver and steatohepatitis (18), higher HCC incidence, and increased tumor size compared to FBXL5 intact mice, indicating that deficiency of FBXL5 is involved in hepatic carcinogenesis (19). Alterations in iron metabolism-related proteins seem to be related with the prognosis of diverse cancers, such as prostate, breast, pancreatic and esophageal cancer, and renal cell carcinoma (20)(21)(22)(23)(24). However, FBXL5 expression and its clinical implications have not yet been reported in samples from patients with HCC.…”
mentioning
confidence: 99%